DAMPAK MOTIVASI KERJA DALAM UPAYA PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PT. ALAM PERMATA RIAU KABUPATEN KAMPAR - Putra, Eka (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
Abstract, This research was conducted at PT. Alam Permata Riau Sub-district Siak Hulu District Kampar, which aims to determine the effect of work motivation on employee work productivity. In analyzing the data obtained from the object of research using descriptive and quantitative methods with the number of respondents 47 people, comparing the actual reality with theories that have a relationship with the problem in order to draw conclusions and tabulated in tabular form then analyzed according to research objectives. The results of the discussion can be concluded that work motivation has a significant effect on employee work productivity, this can be seen from the effect of work motivation indicators with employee work productivity indicators. It is known that the value of t count> t table (5.875> 2.014) and significant <0.05 (0.000 <0.050) so Ho is rejected, which means that work motivation has a significant effect on work productivity. It is also known that the R square (ð‘…2) of 43.4% or 0.434 is used to determine the percentage of the influence of the independent variable (Work Motivation) on the dependent variable (Work Productivity). The R square means that work motivation contributes to changes in employee work productivity variables by 43.4% and the rest is influenced by other factors that are not discussed in this study. Therefore, it is expected that PT. Alam Permata Riau Sub- district Siak Hulu District Kampar to further increase employee motivation to achieve the work productivity expected by the company.